PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN PT. POS INDONESIA (PERSERO) - Yahya, M (At-Tafkir, 2016)
This study aims to identify and analyze leadership styles, organizational commitment and employee performance and influence of leadership style and organizational commitment to employee performance, both simultaneously and partially at PT. Pos Indonesia (Persero). The method used is survey explanation method on 87 employees of PT. Pos Indonesia (Persero). Techniques used to test the hypothesis is that the path analysis (path analysis). Research results through descriptive analysis shows that the leadership style of leader PT. Pos Indonesia (Persero) is an employee-oriented leadership style. In general, the leadership style at PT. Pos Indonesia (Persero) is in the high category. Task oriented leadership styles at appropriate category and employee oriented leadership style is in the high category. If viewed from the organizational commitment was generally high category. Affective commitment and normative commitment are included in the high category while kontinuens commitment is in the category enough. Viewed from the employee's performance in general is in the high category. Quality, the need for supervision and the influence of personal relationships, including in the high category and quantity of output, timeliness and cost effectiveness is in the category so it must be increased. Furthermore, the results showed that leadership style and organizational commitment have a positive and significant influence either partially or  simultaneously on employee performance.